A lightweight and high thermal performance graphene heat pipe. Issue 2 (27th November 2020) - Liu, Ya; Chen, Shujing; Fu, Yifeng; Wang, Nan; Mencarelli, Davide; Pierantoni, Luca; Lu, Hongbin; Liu, Johan
Abstract: Heat pipe is one of the most efficiency tools for heat dissipation in power systems. Currently, heat pipes are usually made of copper or aluminum. However, due to their relatively high density and limited heat transmission capacity, heat pipes are facing urgent challenges in power electronics. In this paper, a new class of graphene enhanced heat pipe that can cope with these issues is reported. The graphene enhanced heat pipe is made of high thermal conductivity graphene assembled film with nanostructure enhanced inner surfaces. The study shows that the dramatically improved heat dissipation capacity, 7230 W m −2 K −1  g −1, about 3.5 times higher than that of copper based commercial heat pipes can be achieved. This paves the way for using graphene enhanced heat pipe in lightweight and large capacity cooling applications, as required in many systems such as automotive electronics, hand‐sets and space electronics. Abstract : A new class of lightweight and highly specific thermal transfer coefficient graphene heat pipe (GHP) is firstly fabricated in this work. Such GHP exhibits a cooling capability up to 7230 W m −2 K −1  g −1, which is about 3.5 times better than that of commercial copper based heat pipe (2053 W m −2 K −1  g −1 ).